Measures to Remove Geothermal Energy Barriers in the European Union - Antonio Colmenar-Santos; Elisabet Palomo-Torrejón; Enrique Rosales-Asensio; David Borge-Diez (Energies, 2018)
This article examines the main market barriers that hamper the introduction of geothermal energy at local, national, and European levels as well as the necessary steps that need to be taken to eradicate them, thus contributing to the general use of this renewable source of energy. The novelty of this study lies in the detailed description of four different scenarios: the European Union (EU), Spain, the Canary Islands, and the agricultural sector for the three types of geothermal energies and their uses: Low-enthalpy or thermal uses, high-enthalpy or electrical uses and renewable energy mix. The results are expected to differ in terms of level of introduction, barriers, and measures to be taken. We have selected Spain within the European context due to its meagre 0.1% geothermal market share in primary demand for renewable energy, and the Canary Islands in particular, given its insular nature. We have likewise picked the agricultural sector due to its underdevelopment as far as renewable energies are concerned, including geothermal energy.